2018
DOI: 10.1093/dote/doy016
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition therapy in esophageal cancer—Consensus statement of the Gastroenterological Society of Taiwan

Abstract: A number of clinical guidelines on nutrition therapy in cancer patients have been published by national and international societies; however, most of the reviewed data focused on gastrointestinal cancer or non-cancerous abdominal surgery. To collate the corresponding data for esophageal cancer (EC), a consensus panel was convened to aid specialists from different disciplines, who are involved in the clinical nutrition care of EC patients. The literature was searched using MEDLINE, Embase, the Cochrane Central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Patients with esophageal cancer usually experience significant weight loss and have a high risk for malnutrition (2,17), because both the severity of the illness and the multimodal oncological treatment threatens patients' nutritional status. Malnutrition results from an inadequate intake or absorption of nutrients and leads to measurable adverse effects on body weight, body composition, function and clinical outcomes (18).…”
Section: Malnutritionmentioning
confidence: 99%
“…Patients with esophageal cancer usually experience significant weight loss and have a high risk for malnutrition (2,17), because both the severity of the illness and the multimodal oncological treatment threatens patients' nutritional status. Malnutrition results from an inadequate intake or absorption of nutrients and leads to measurable adverse effects on body weight, body composition, function and clinical outcomes (18).…”
Section: Malnutritionmentioning
confidence: 99%
“…Dysphagia, odynophagia and GOO are common consequences of cancer [12][13][14][15]. Several techniques are available to deal with these conditions and optimize nutritional support mostly in two different situations: when pa-tients are under cancer treatment with curative intent (chemotherapy, radiotherapy or awaiting surgical resection) or when they are referred for symptom palliation in cases of advanced disease and a poor performance status.…”
Section: Techniques Of Nutritional Support For Cancer Patients Withoumentioning
confidence: 99%
“…Upper GI obstruction is a usual consequence of digestive cancer with a potential negative impact on patients' nutritional status and quality of life [4,6]. Head and neck (H&N) cancer, particularly pharyngeal and laryngeal lesions, oesophagogastric tumours and all neoplasia causing gastric outlet obstruction (GOO), such as tumours of pancreatic, hepatobiliary and duodenal origin, are important causes of intolerance to oral intake [12][13][14][15]. In fact, gastroenterologists play a central role in the nutritional management of cancer patients through their endoscopic techniques that allow maintenance of oral and/or enteral feeding.…”
Section: Introductionmentioning
confidence: 99%
“…The Taiwan Society of Gastroenterology, in patients undergoing esophagectomy, suggest the superiority of jejunostomy over the nasoenteral catheter, since the former has lower indices of displacement and interruption of the nutritional support. Nevertheless, they concluded that, in randomized studies, there is no evidence of the superiority of one nutritional route over the other (45).…”
Section: Comparative Studies Between Jejunostomy and Nasojejunal Cathmentioning
confidence: 99%